Exploring Mental Health Stigmatization within AAPI Communities - Kayla Lankford:::::: (2024)
My final project for SOC 349: Asian American and Pacific Islander Communities was a creative capstone of poems about the mental health stigmatization in Asian American communities. This course followed the history of different Asian American groups and their different journeys into the United States. The CSUSM Library Award for Undergraduate Research, Scholarship and Creative Activity recognizes undergraduate students who demonstrate sophistication and originality in research projects and creative works, and reflection upon the research/creation process. Up to six prizes will be awarded in three categories: Creative Works, Empirical Research and Interpretive Analysis. Winners receive a cash prize and public recognition of their excellent work. Submissions by individuals or groups will be considered in the following three categories: Creative Works, including, but not limited to, an art installation, software program, musical composition, film or video, special project, etc. Empirical Research, including, but not limited to, research conducted with qualitative or quantitative methodologies using the (social-) scientific method. Interpretive Analysis, including, but not limited to, analysis which aims to capture hidden meaning and ambiguity of a cultural artifact.